Hubungan Durasi Penggunaan Gawai dengan Kejadian Astenopia pada Mahasiswa Program Studi Keperawatan saat Pandemi COVID-19: Correlation between Gadget Usage Duration with Asthenopia Incidence in Nursing Students during Covid-19 Pandemic - Delia Mentari; Mita Mita; Argitya Righo (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Asthenopia is a subjective complaint of the eye caused by a disturbance in the accommodation system of the eye related to activities such as the use of gadgets. Symptoms of asthenopia can be ocular symptoms, visual symptoms and extraocular symptoms. This research aims to identify the correlation between gadget usage duration with asthenopia incidence. Determination of the sample using stratified random sampling and followed by purposive sampling technique so that the number of respondents obtained as many as 203 people. The instrument used consisted of a questionnaire on the duration of the use of the device and the Visual Vatigue Index. It was analysed by Spearman rho correlation test. The results showed that 3.9% of respondents use gadget with light duration, 79.8% with moderate duration and 16.3% with heavy duration. Then 28.6% of respondents did not experience asthenopia and 71.4% of respondents experienced asthenopia and also there was no relationship between the duration of device use and the incidence of asthenopia (p=0.422 or p>0.05). There is no relationship between the duration of device use and the incidence of asthenopia in Nursing Study Program students during the COVID-19 pandemic. Keywords: Gadget Usage Duration, Asthenopia, Nursing Student Abstrak Astenopia merupakan keluhan subjektif pada mata yang disebabkan adanya gangguan pada sistem akomodasi mata yang berkaitan dengan aktivitas yang dilakukan seperti penggunaan gawai. Gejala astenopia dapat berupa gejala okuler, gejala visual dan gejala ekstraokuler. Penelitian ini bertujuan untuk mengidentifikasi hubungan durasi penggunaan gawai dengan kejadian astenopia. Penentuan sampel menggunakan stratified random sampling dan dilanjutkan dengan teknik purposive sampling sehingga jumlah responden yang diperoleh sebanyak 203 orang. Instrumen yang digunakan terdiri dari kuesioner durasi penggunaan gawai dan Visual Vatigue Index. Uji hipotesis menggunakan uji korelasi Spearman rho. Hasil analisa data didapatkan 3,9% responden memiliki durasi penggunaan gawai ringan, 79,8% durasi penggunaan gawai sedang dan 16,3% durasi penggunaan gawai berat. Kemudian 28,6% responden tidak mengalami astenopia dan 71,4% responden mengalami astenopia serta tidak terdapat hubungan antara durasi penggunaan gawai dengan kejadian astenopia (p=0,422 atau p>0,05). Tidak terdapat hubungan antara durasi penggunaan gawai dengan kejadian astenopia pada mahasiswa Program Studi Keperawatan saat pandemi COVID-19. Kata Kunci: Durasi Penggunaan Gawai, Astenopia, Mahasiswa Keperawatan